Some Special Problems in Peritoneal Dialysis 2016
DOI: 10.5772/63504
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis Solutions

Abstract: Conventional peritoneal dialysis PD solutions are characterized by several undesirable characteristics, including acidic pH . . , high glucose concentrations . . g/L , hyperosmolarity mOsm/kg and relatively high concentrations of glucose degradation products GDPs . These characteristics have been shown to result in adverse clinical outcomes, including acute peritoneal membrane toxicity manifested as inflow pain , chronic peritoneal toxicity including membrane failure, ultrafiltration failure, peritonitis and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 237 publications
1
5
0
Order By: Relevance
“…In the present per-protocol analysis of the balANZ trial, after adjusting for a range of demographic, clinical and dialysis characteristics, the use of biocompatible PD solution was associated with 27% better preservation of RRF (p = 0.004) and 37% better preservation of residual urine volume (p < 0.001) compared with the use of conventional PD solution. These findings are in keeping with the consistent findings of systematic reviews and meta-analyses of RCTs that biocompatible PD solutions better preserve RRF and residual urine volume compared with conventional solutions (24)(25)(26)(27)(28)(29). The results of the present study therefore further support these systematic reviews and the recommendations of the International Society for Peritoneal Dialysis (ISPD) guidelines that neutral pH, lowglucose degradation product PD solutions should be used for better preservation of RRF (2).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present per-protocol analysis of the balANZ trial, after adjusting for a range of demographic, clinical and dialysis characteristics, the use of biocompatible PD solution was associated with 27% better preservation of RRF (p = 0.004) and 37% better preservation of residual urine volume (p < 0.001) compared with the use of conventional PD solution. These findings are in keeping with the consistent findings of systematic reviews and meta-analyses of RCTs that biocompatible PD solutions better preserve RRF and residual urine volume compared with conventional solutions (24)(25)(26)(27)(28)(29). The results of the present study therefore further support these systematic reviews and the recommendations of the International Society for Peritoneal Dialysis (ISPD) guidelines that neutral pH, lowglucose degradation product PD solutions should be used for better preservation of RRF (2).…”
Section: Discussionsupporting
confidence: 90%
“…However, the observed renoprotective benefit of biocompatible solutions was independent of peritoneal UF. Moreover, previous systematic reviews of RCTs have demonstrated a consistent renoprotective benefit of biocompatible PD solutions despite the fact that there was no evidence that these solutions exerted a significant effect on peritoneal UF (24,25,28,29).…”
Section: Discussionmentioning
confidence: 94%
“…They include, neutral pH, low or ultralow glucose degradation products containing solutions, solutions using alternative osmotic agents, low-sodium solutions and supplementation with the dipeptide alanyl-glutamine. [28][29][30][31] The peritoneal administration of alanylglutamine -a dipeptide with immunomodulatory effects -in uremic rat and mouse PD exposure models showed substantial promise, as it reduced PD-induced peritoneal fibrosis, reduced proinflammatory/fibrotic markers and ameliorated damage, in part by modulating IL-17 expression. 31 At present, however, in spite of demonstrating some beneficial effects in maintaining stability of PSTR, there is no conclusive clinical evidence that the use of more bio-compatible PDS is associated with a lower burden of peritoneal inflammation or improved clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose in PD solutions is absorbed and contributes to a number of potential systemic adverse effects, including poor glycemic control, weight gain, dyslipidemia, and increased cardiovascular risk (3 4 5 6 7 8 9-10). Furthermore, the glucose in PD solutions causes damaging local membrane effects, such as membrane thickening and vasculopathy, and immunological effects, such as stimulated inflammatory cytokine secretion and impaired phagocytosis (11,12), perhaps through the effects of advanced glycosylated end-product (AGE) formation and direct cytotoxicity of glucose degradation products (GDPs) on the peritoneum (3,1320). These local effects may contribute to changes in membrane transport characteristics (21,22), which in turn may adversely affect technique and patient survival (10,23,24).…”
mentioning
confidence: 99%